2013
DOI: 10.1016/j.jimonfin.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Credit-risk valuation in the sovereign CDS and bonds markets: Evidence from the euro area crisis

Abstract: We analyse the extent to which prices in the sovereign credit default swap (CDS) and bond markets reflect the same information on credit risk in the context of the current crisis of the European Monetary Union (EMU). We first document that deviations between CDS and bond spreads are related to counterparty risk, common volatility in EMU equity markets, market illiquidity, funding costs, flight-to-quality, and the volume of debt purchases by the European Central Bank (ECB) in the secondary market. Based on this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 30 publications
3
48
2
1
Order By: Relevance
“…corporate market: if this market is driven more by informed trading, then price discovery may occur in the least transparent market that might tend to be the less liquid market). This contrasts with Arce et al's findings that are discussed further below, which found that the degree of liquidity does not affect price discovery (Arce et al 2013) Commission Task Granger causality tests find price discovery is equally likely to occur in either market (for Greece and Italy, the bond market seemed to be the more important market; for Spain and Ireland, the CDS market seemed to be more important; for Portugal, it went both ways)…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…corporate market: if this market is driven more by informed trading, then price discovery may occur in the least transparent market that might tend to be the less liquid market). This contrasts with Arce et al's findings that are discussed further below, which found that the degree of liquidity does not affect price discovery (Arce et al 2013) Commission Task Granger causality tests find price discovery is equally likely to occur in either market (for Greece and Italy, the bond market seemed to be the more important market; for Spain and Ireland, the CDS market seemed to be more important; for Portugal, it went both ways)…”
Section: Resultscontrasting
confidence: 60%
“…Seretakis also notes that in cases where price changes in the CDS market did lead changes in the underlying bond market, the changes in CDS spreads were linked to fundamentals responding to country-specific events, see ibid, at p. 135. 77 Arce et al (2013), at p. 127; Levy (2009), at p. 35. Levy's findings also suggested that changes in the relative liquidity in the two markets could explain why there was no consistent pattern of one market leading the other.…”
mentioning
confidence: 99%
“…Instead, the present 5 In reduced-form models, a default is modeled as the …rst arrival of a risk-neutral Poisson process whose stochastic intensity process is represented by Q t . For more details, see Bielecki and Rutkowski (2002).…”
Section: The Pricing Modelmentioning
confidence: 99%
“…This is a bilateral contract in which the buyer pays a periodic fee or premium in exchange for a contingent payment by the counterparty (the seller) in the case of credit event occurs (a review about the CDS market can be seen in Moorad (2006)). The literature presents a lot of works related to credit default swaps, covering several aspects and approaches of this instrument such as spillovers, correlations and determinants (see for example Bruyckere et al, 2013;Oliveira, Curto, & Nunes, 2012;Naifar, 2011;Arce, Mayordomo, & Pena, 2013).…”
Section: Introductionmentioning
confidence: 99%